2017
DOI: 10.2174/1874836801711010136
|View full text |Cite
|
Sign up to set email alerts
|

The Information Requirements for Transportation Industry’s Facilities Management Based on BIM

Abstract: In recent decades, Building Information Modeling (BIM) is well-known and has been widely accepted by AEC industry since it could make less mistakes, conflicts, and bring more profits as well as improve the level of communication and coordination. However, in the Operation and Maintenance phase, most of the owners including the transit agencies, still lack the knowledge about what BIM deliverables and processes to demand and how to facilitate and encourage other stakeholders to apply BIM technology. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…In the end, within infrastructures, Valdepeñas et al [69] concentrate on port infrastructures, applying BIM for its management and conservation; Besenyoi et al [71] discuss the case of the Tempelhof airport, focusing on ordinary management tasks or event management purposes; and Liu and Gao [72] aim to support public authorities in adopting BIM for FM.…”
Section: Building Typologymentioning
confidence: 99%
“…In the end, within infrastructures, Valdepeñas et al [69] concentrate on port infrastructures, applying BIM for its management and conservation; Besenyoi et al [71] discuss the case of the Tempelhof airport, focusing on ordinary management tasks or event management purposes; and Liu and Gao [72] aim to support public authorities in adopting BIM for FM.…”
Section: Building Typologymentioning
confidence: 99%
“…Actor barriers, as shown in Table 3, were almost entirely concerned with areas associated with members' knowledge, skills and abilities (KSAs). Sources: (Badi and Diamantidou, 2017;Comiskey et al, 2017;Gu and London, 2010;Hosseini et al, 2018;Kent and Becerik-Gerber, 2010;Kihong Ku and Mahabaleshwarkar, 2011;Kokkonen and Alin, 2016;Liu and Gao, 2017;Matthews et al, 2018;Olatunji, 2011a;Pikas et al, 2013b;Sackey et al, 2015;Solnosky et al, 2014;Succar, 2009) In this regard, studies by Kokkonen and Alin (2016), Solnosky et al (2014) and Pikas et al (2013b) indicated that even those organisations currently implementing BIM still struggle with training and access to employees who possess the skills to use BIM to manage and collaborate. In other words, lack of necessary skills, particularly interdisciplinary communications and collaboration competencies have not been improved to match BIM developments (Kokkonen and Alin, 2016).…”
Section: Actor Barriersmentioning
confidence: 99%
“…However, the finding of the study also needs to be tested within empirical settings to further validate applicability in real-life projects. Other efforts focused on addressing information needs for transportation [60], education [46,57,77,101] and cultural heritage [64,102]. In addition, information requirements and clients' needs to improve asset management were investigated to enhance the BIM integration [62,84,[103][104][105].…”
Section: Information Requirementsmentioning
confidence: 99%
“…Additionally, the design and construction phases of projects are synonymous with creating numerous files with different formats. These files become incompatible at a later phase, especially when using BIM and require modifications and re-processing which requires effort and time, and most importantly, raises the issue of interoperability [8,9,60]. This forms another issue of losing data throughout the format exchanging process.…”
Section: Technical Barriersmentioning
confidence: 99%
See 1 more Smart Citation